The ethical principles of the Portuguese psychologists : an evaluation after eleven years - Ricou, Miguel (2024)
Abstract: Several changes were implemented in the psychology profession after the Order of Portuguese Psychologists was created. A set of ethical principles to guide psychological practice was established. Eleven years after the several changes have been initiated in the professional practice in Portugal, this study analyzes whether there are changes in the valuation of the fundamental ethical principles of Portuguese psychologists. To this end, data from 2009 and 2020 was compared. On a grading scale from 1 to 5, Portuguese psychologists allotted the importance to each general principle. We found Competence and Responsibility decreased after 11 years, and Integrity and Beneficence and Non-Maleficence increased from 2009 to 2020. We also found that Psychologists with more experience valued more the Respect for people’s rights and dignity, Integrity, and Beneficence and nonmaleficence than those with lesser years of experience. Order of Portuguese Psychologists and the existence of an ethics code seems to have improved the professional identity.